Exploring chat-based communication in the EFL class: computer and mobile environments - Andujar, Alberto; Salaberri-Ramiro, Maria Sagrario (Computer assisted language learning, 2021)
This study investigates the use of computer-mediated and mobile-mediated chat-based communication in an EFL course and seeks to explore differences between both modes of communication in order to better understand their potential to foster language development. Factors such as engagement, timing, participation, addressivity, speakership roles, type/retype messages, average message length and students' perceptions are evaluated in both environments. A total of 64 Spanish students taking a B1 English course at the University of Almería were studied. According to treatment type, subjects were divided in two groups, one in which the WhatsApp application was used to represent mobile chat-based communication and another using Facebook to represent computer chat-based conversation. Two chat groups were created, one on each application, where 32 students in each group participated in daily interaction over four months. Pre and post surveys analysing students' engagement were given to participants in both groups. Messages were tracked and samples of both types of communication were used to explore differences between the two environments. An end-of-course survey was also used to evaluate students' perceptions of the interaction as well as each of the contexts under investigation. Findings highlighted significant differences between cognitive engagement and emotional engagement in the computer and mobile environments. Furthermore, differences between the two environments were also found regarding timing, perceived value of the interaction, use and participation.